An assessment of and perspective on the measurements and indicators of governance in South Africa - Vezi, Nkosiyezwe Cyprian (University of the Free State, 2017)
As a leading post-colonial nation-state in the African continent, South Africa finds itself in desperate period to foster better good governance, especially in the wake of an ailing economy marred by mass corruption. The study explores the use of governance indexes to foster greater good governance practices. The purpose of the study was to determine the impact of the Governance Indicators reports on state behaviour in South Africa. The study does this by using a qualitative research design to address the four research objectives. The four research objectives of the study were (i) To determine the extent to which Governance Assessment reports are recognized by South Africa (ii) To determine the governance index recognized by SA in comparison to other governance indexes; (iii) To determine the impact of governance indices on state behaviour; (iv) To determine the extent to which governance reports have the ability to police South Africa. A content analysis technique is used to analyse the South African Parliament Hansard Documents, the Presidency’s Annual Reports and the State of Nation Address and to achieve the objectives of the study. The content analysis results revealed that the governance indexes are still relevant in South Africa to foster good governance; however, are not recognised in Parliament as tools to influence nation state behaviour. The study findings show that the achievement of good governance in South Africa is congruent with the achievement of the NDP goals and reveals that there have been significant efforts made to achieve the NDP goals. The study showed weak political leadership in South Africa is the primary cause of the many issues which derail good governance efforts in the country. The study recommends that South Africa must accelerate its efforts to achieve its NDP goals as they are congruent with good governance practises by building and strengthening institutions that foster good governance.
Dissertation (M. (Political Studies))--University of the Free State, 2017
Keywords: Political indicators; Governors -- South Africa; Africa -- Politics and government